DIAGNOSTICO DE LA SUSCEPTIBILIDAD Spodoptera frugiperda A INSECTICIDAS CON DIFERENTES MODOS DE ACCIÓN - Calvache Ibalbo, Iván Joseph (2024)
The importance of this research lies in generating efficient strategies for the control of fall armyworm, optimizing integrated pest management (IPM), and reducing insecticide resistance. The objective was to diagnose the susceptibility of Spodoptera frugiperda to insecticides with different modes of action. Laboratory tests were conducted with four insecticides: Flubendiamide, Spinetoram, Emamectin benzoate, and Lufenuron, using both commercial and diagnostic doses. The study was conducted at the Chemistry and Biochemistry Laboratory of the "La María" campus, using a completely randomized experimental design.